Hubungan antara Kecerdasan Emosi dan Humor pada Remaja - Erik Wijaya; Debora Basaria (Fakultas Psikologi Universitas Tarumanagara, 2016)
Humor is the nature of something or complex situations that give rise to a desire to be together. Simply put humor is defined as something funny. Eysenck cited in Utomo (2009) mention the humor is something that can make laugh. Humor is considered to lead to positive emotions. Humor can make a person more relaxed, not tense, so that the mind can be more concentrate to solve the problem. Teens in completing development tasks known to use humor as part of coping in resolving the problem. Content in the humor involves the presence of such intelligence emotional intelligence. This study is aimed to see the correlatiom between emotional intelligence and humor in adolescents. Participants in this study involving 300 adolescents aged 11-20 years in Jakarta. Measurements in this study using a instrument that measuring emotional intelligence and measuring humor. The results of this study found a positive relationship between emotional intelligence and humor neutral.Keywords: Humor, emotional intelligence, adolescence